Food handling practices and sanitary conditions of charitable food assistance programs in eThekwini District, KwaZulu-Natal, South Africa - Sizwe Makhunga; Khumbulani Hlongwana (Scientific Reports, 2024)
Abstract Unsafe food handling practices by food handlers have dire health and financial implications worldwide. Each year, approximately 600 million people, or about 1 in 10 people, are said to become ill from eating contaminated food, and 420,000 people inadvertently die. According to the 2019 World Bank report on the economic burden of foodborne diseases, the annual cost of treating foodborne illnesses is estimated to be US$ 15 billion, and the total productivity loss caused by foodborne diseases in low- and middle-income countries is estimated to be US$ 95.2 billion annually. The purpose of this study was to assess the food handling practices and sanitary conditions of the charitable food assistance programs (CFAPs) in the eThekwini District of KwaZulu-Natal, South Africa. A descriptive cross-sectional study was conducted among 196 CFAPs in eight study settings across five municipal planning regions (MPRs) of the eThekwini District between January 2021 and May 2021. Data were collected using a standardized 37-item observational checklist and analysed through Stata Statistical Software (TX: StataCorp. 2021 LLC.: Release 17. College Station). Compliance levels were calculated using the compliance score (C-score), whereby 0.0–0.20 (0–20%), 0.21–0.40 (21–40%), 0.41–0.60 (41–60%), 0.61–0.80 (61–80%), and 0.81–1.00 (81–100%) were determined as very poor, poor, average, good, and very good, respectively. Statistically significant associations were declared at p < 0.05. Compliance with food hygiene, storage, and packaging was very poor (C-score = 0.003), as were personal hygiene and staff facilities (C-score = 0.147), as well as product information/labelling (C-score = 0.003). Similarly, waste management and pest control systems (C-score = 0.203), compliance with health and hygiene education/training (C-score = 0.335), as well as use and maintenance of transport (C-score = 0.333), all scored ‘poor’. Only the design of premises and facilities had an average compliance score (C-score = 0.43). Given CFAPs’ role in mitigating the impact of poverty, their strict compliance with hygiene protocols is of utmost importance. Systems for identifying and correcting common noncompliance in CFAPs are required.